THE ABILITY OF INDONESIAN UNDERGRADUATE STUDENTS IN PARAPHRASING ACADEMIC WRITING TEXTS - Setiawan, Faisal Ari; Abduh, Amirullah; Baa, Sultan (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2023)
The aims of this study were to find out the English students’ ability in paraphrasing academic writing texts and the students’ perceptions of paraphrasing academic writing texts. The researcher applied a case study research design. The data collection used mixed-methods (quantitative and qualitative data). The data for this research were collected through test and an interview. The researcher employed the test as an instrument to discover the students' ability to paraphrase academic writing texts. Meanwhile, interviews were conducted to reveal students' perceptions of paraphrasing in academic writing texts. The sample for the test were 31 students. All participants for the test must meet the following criteria: Participants must be currently enrolled as students in the English Study Program and must be registered in an academic writing class. The test given to students focuses on four aspects by Jordan (1999), namely paraphrasing by changing synonyms, verb forms, word classes, and synthesis. In the interview session, seven students were selected for the interview. They were selected based on their respective abilities. This was done to make the students' perceptions more varied. The results of the study showed that students' paraphrasing ability by replacing vocabulary with synonyms were in the excellent category with the percentages of 67.74% and paraphrasing ability by replacing verb forms (active and passive) were also in the excellent category with the percentages 48.38%. However, students' ability to paraphrase by replacing word classes were in the unsatisfactory category, with student percentages of 70.96% and students' ability to paraphrase by synthesizing sentences were also in the unsatisfactory category, with student percentages of 48.38%. In the terms of students’ perceptions of paraphrasing academic writing text, the study found that despite many challenges students face in paraphrasing academic writing texts such as students lack of vocabulary, grammatical problems, and difficulty understanding the text, students believe that by doing strategies such as reading widely, practicing regularly, and improving skills, as well as support from lecturers, students can improve their paraphrasing skills for the better